Effect of Growth Regulators on In Vitro Micropropagation of Potato (Solanum tuberosum L.) Gudiene and Belete Varieties from Ethiopia - Sunil Tulshiram Hajare; Nitin Mahendra Chauhan; Girum Kassa (The Scientific World Journal)
Aim. Potato (Solanum tuberosum L.) is one of the important crops in Ethiopia which has a crucial role in nutritional security, poverty alleviation, and income generation. The aim of the present investigation is to develop an efficient in vitro propagation protocol for Belete and Gudiene potato varieties by using lateral bud as explants. Materials and Methods. Shoot initiation was achieved by inoculating buds on full-strength MS Murashige and Skoog medium (MS) fortified with variable concentrations of BAP and NAA. Basal MS was used as control throughout the experiment. Results. Results of our study showed that best shoot initiation was obtained on MS medium supplemented with 1.5 mg/l BAP + 3.0 mg/l NAA for Gudiene variety, whereas 1.0 mg/l BAP and 2.0 mg/l NAA produced more shoots in Belete variety. The initiated shoots increased two- to three-fold upon subculture on the MS medium fortified with varying concentrations of BAP and Kinetin. The highest numbers of multiple shoots were obtained in the MS medium containing 2.5 mg/l Kinetin. The combined effect of BAP and Kinetin did not produce any additional positive effect for shoot multiplication. Rooting percentage and number of roots/shoot were found best on the MS medium fortified with 1.0 mg/l IBA + 0.5 IAA. Conclusions. The variety Gudiene was found best for shoot initiation and root formation, while Belete variety proved its superiority for multiple shoot formation. A total number of 82.66% of plantlets were acclimatized under field conditions. This work indicates the practical applicability of plant tissue culture using lateral bud as explants is effective for micropropagation of potato in vitro.